Ethnicity as a factor in the subjective experience of loneliness in students - Yu. M. Zabrodin; E. L. Soldatova; O. O. Andronnikova; Yu. M. Perevozkina (Russian State Vocational Pedagogical University, 2023)
Introduction. The phenomenon of loneliness is multidimensional and ambiguous. Attitudes to loneliness are heterogeneous and mediated, among many factors, by cultural and ethnic features. Territorial proximity and historically conditioned relations and migrations of Ural-Siberian territories and Kazakhstan allow conducting intercultural and interethnic research. This research is devoted to the study of specifics of loneliness experience by first-year students - representatives of these nations. The problem of loneliness becomes especially urgent as a result of growth of anxious and depressive states, and sometimes suicidal and victim behaviour among first-year students.Aim. The aim of the current research is to identify ethnic aspects of the subjective experience of loneliness of first-year students studying in Russia and Kazakhstan. The research examines the specifics of experiencing loneliness by students of different ethnic backgrounds (Russians, Kazakhs), 197 students (119 males and 78 females).Research design. The research design involved the determination of loneliness factors for the entire empirical sample (factor analysis) with subsequent calculation of the values of the received factors for each respondent. Then students were compared separately for boys and girls of Kazakh and Russian ethnicity.Measurements. To conduct the research, the authors used a set of methods to study loneliness, Zung Self-Rating Depression Scale and a questionnaire to identify the level and nature of loneliness by G. R. Shagivaleeva.Results. The authors found that the component composition of loneliness can be represented by three factors: depressive experience of loneliness, positive experience of loneliness, experience of loneliness in interpersonal relationships. It was revealed that students of Kazakh ethnicity expressed a negative perception of loneliness (p = 0.007), actualising depressive tendencies. A positive experience of loneliness is more characteristic of girls than boys (p = 0.02). For girls of Kazakh ethnicity, separation from the parental family enhances the feeling of loneliness (p < 0.05).Scientific novelty. The presented research results confirm the multidimensional nature of the phenomenon of loneliness, which determines the ambiguity of attitudes towards it and gives special weight to the value attitude towards loneliness in culture. Differences in the experience of loneliness by students, due to the specifics of ethnic attitudes, are revealed. Theoretical significance of the study is determined by the identified regularities in the component composition of the experience of loneliness by students of two ethnic groups (Russians and Kazakhs), its content and gender-role specificity.Practical significance. Empirical data contribute to the understanding of the ethnic characteristics of students' experiences of loneliness and can serve as the basis for the development of university programmes that enhance psychological well-being.